2019
DOI: 10.3349/ymj.2019.60.12.1195
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Attenuates Hypoxia/Reoxygenation-Induced Apoptosis and Autophagy in HK-2 Cells by Inhibiting JNK Activation

Abstract: PurposeThe aim of this study was to investigate whether propofol could attenuate hypoxia/reoxygenation-induced apoptosis and autophagy in human renal proximal tubular cells (HK-2) by inhibiting JNK activation.Materials and MethodsHK-2 cells were treated with or without propofol or JNK inhibitor SP600125 for 1 hour and then subjected to 15 hours of hypoxia and 2 hours of reoxygenation (H/R). Cell viability and LDH release were measured with commercial kits. Cell apoptosis was evaluated by flow cytometry. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Subsequently, it was confirmed that the apoptotic events in NRK-52E cells cultivated under high UA levels were dependent on ROS generation. Inhibition of ROS has been demonstrated as protective in several experimental cell models, such as hypoxia reoxygenation, unilateral ureteral obstruction (UUO), chronic renal failure and diabetic nephropathy ( 45 48 ). The findings of the present study offered an explanation for the renal cell protective effects of ROS scavengers.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it was confirmed that the apoptotic events in NRK-52E cells cultivated under high UA levels were dependent on ROS generation. Inhibition of ROS has been demonstrated as protective in several experimental cell models, such as hypoxia reoxygenation, unilateral ureteral obstruction (UUO), chronic renal failure and diabetic nephropathy ( 45 48 ). The findings of the present study offered an explanation for the renal cell protective effects of ROS scavengers.…”
Section: Discussionmentioning
confidence: 99%
“…The association between propofol and autophagy is complex. For example, propofol attenuates hypoxia/reoxygenation-induced autophagy in HK-2 cells, but induces autophagy in C2C12 cells (16). The present study aimed to elucidate the antitumor molecular mechanism of propofol on human lung adenocarcinoma cells and its potential application on lung cancer therapy.…”
Section: Introductionmentioning
confidence: 94%
“…Autophagy is a conserved complex process which maintains the normal function and structure of cells (15,16). Autophagy is involved in the occurrence and progression of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of caspase-3 in RAW264.7 cells was detected using Caspase-3 Activity Assay Kit (Beyotime Institute of Biotechnology, China) following the manufacturers' instructions. In short, 100 μL lysate was added into the RAW264.7 cells for 15 min on dry ice and centrifuged (20,000 g, 4°C) 15 min, then 50 μL supernatant, 40 μL detection buffer, and 10 μL caspase-3 substrate acetyl-Asp -Glu-Val-Asp p-nitroanilide (2 mM) 16 were added into 96well plates for 60 min. The absorbance of p-nitroanilide was determined at 405 nm using a microtiter plate reader (Bio-Rad, USA).…”
Section: Caspase-3 Activity Assaymentioning
confidence: 99%
“…14,15 Controlling the pathological changes and protecting the tissue from damage is a usual strategy. ID13 remarkably alleviated pathological status, inhibited the production of pro-inflammatory cytokines, 16 and suppressed the TLR2-NF-κB signal pathway. 17 Daphnetin conferred protection against S. aureus-induced pneumonia by anti-inflammation and enhanced mTOR-dependent autophagy.…”
Section: Introductionmentioning
confidence: 97%